Analisis Akurasi Beberapa Persamaan Angkutan Sedimen Tak Berdimensi Terhadap Persamaan Einstein (1950) - Junaidi Junaidi (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2012)
Bottom of the river is always composed of a mixture of sediment in non uniform and the grain size distribution in the phase of the transported sediment is generally smoother than the distribution of basic material due to selective transport. This makes estimates of sediment transport in natural rivers is difficult; although it has provided the basic sediment transport equations are quite a lot, there is still controversy regarding its performance. This paper analyzes the accuracy of the count of the basic sediment transport using a dimensionless transport equations of Julien (2002), Brown (1950), Parker (1979), Engelund et Fredsoe (1976), Graf & Suszka (1987), Meyer-Peter & Mueller (1948), and Recking (2006) compared to Einstein (1950) formula. Methods discrepancy ratio (r) is used to demonstrate the suitability of the good (goodness of fit) between the results calculated for comparison. Based on the spread of the data on the graph of a diagonal line (line of perfect agreement) and on the basis of the percentage of data in the range of discrepancy ratio values are given, a matter of sediment transport parameters using the equations of Graf & Suszka give the most close to the matter of using the Einstein equation, compared with six other counts equation.